THE EFFECT OF BROILER CHICKEN MEAT MARINATION USING CUCUMBER SOLUTION (CUCUMIS SATIVUS L) ON MEAT QUALITY - Sanjaya, Ragil Mohamad; Sariri, Ahimsa Kandi (Universitas Veteran Bangun Nusantara, 2025)
Most of the causes of meat spoilage are due to poor handling, which provides opportunities for contamination or growth of spoilage-causing microbes that can affect the quality and shelf life of the carcass. Marination becomes a strategic step in maintaining the quality of meat and extending its shelf life. To maintain the quality of the carcass during storage, the addition of cucumbers containing antibacterial compounds is necessary to inhibit the growth of spoilage-causing microorganisms. The purpose of this study is to determine the effect of soaking chicken meat in cucumber solution on the quality of chicken meat during the storage process. The method used in this study is a Completely Randomized Design (CRD) with four treatments and four replications, differing in storage duration at room temperature (0, 3, 6, and 9 hours). The data obtained were analyzed using the Analysis of Variance (ANOVA) test. If a significant treatment effect is found, it is followed by a comparison test using Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Based on the statistical test, the chemical quality of pH and moisture content, as well as the physical quality of cooking loss, still show values within the standard feasibility range. The results of the ANOVA test show a significant difference in pH and cooking loss values, but no significant effect on moisture content values. Keywords: Chicken meat, Cucumber, pH, Moisture content, Cooking loss